ANALISIS PELATIHAN PENYARINGAN BERITA DI MEDIA SOSIAL TENTANG PANDEMI COVID-19 DAN VAKSINASI KEPADA MASYARAKAT DESA RANTAU PANJANG - T Silvana Sinar; Syahron Lubis; Thyrhaya Zein (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
The ease of access to social media makes the spread of news that cannot be accounted for easily spread nowadays. Likewise, the issue of Covid-19 and vaccination, there has been a lot of fake news circulating about this which is troubling the public. This paper aims to review information that is controversial on social media, especially fake news that is troubling people in cyberspace or often called hoax. The purpose of this paper is to explain the importance of filtering information on social media among the public as a solution to tackling the spread of hoaxes related to the issue of Covid-19 and vaccination. Partners in this activity are the people of Rantau Panjang Village, the implementation of the activity uses the lecture and discussion method. The results of this study indicate that studying and finding out the truth of information is important as an effort to overcome the spread of hoaxes.